Adsorption of Phosphate from Aqueous Solution by Calcination of Silicified Coal: Kinetic and Isotherm Studies - Fandana, Lisa; Abdullah, Faisal; Muslim*, Abrar; Suhendrayatna, Suhendrayatna; Meilina, Hesti (Graduate School of Universitas Syiah Kuala, 2023)
Silicified coal (SC) consisting of SiO2 is a promising raw material for adsorbent. The present study aimed to utilize silicified coal bottom ash (SCBA) adsorbent by calcination of the SC at temperatures of 600, 800, and 1000 oC for 1 hour. The FTIR result showed that the SCBA_600, SCBA_800, and SCBA_1000 had chemical functional groups such as the asymmetric Si-O-Si, the symmetric Si-O-Si and Si-O-Si bond rocking for adsorption of phosphate (PO4 3) with the lowest percentage of transmittance of SCBA-1000. The adsorption test showed that rapid adsorption occurred in the first 10 minutes of contact time, and it did not change significantly for the rest of contact time until reaching an equilibrium time of 30 min. The PO4 3 adsorption efficiency and capacity fluctuated over the initial PO4 3 in solution in the 60.02480.29 mg/L range. The highest PO4 3 adsorption efficiency and capacity were at 480.29 mg/L, 95.49 %, and 45.86 mg/g, respectively, using the SCBA-1000. The adsorption kinetic fitted better to the pseudo-second-order kinetics model (average R2 = 0.999) with the adsorption capacity of 45.454, 45.662, and 45.872 for the SCBA_600, SCBA_800, and SCBA_1000, respectively, and the PO4 3 adsorption rate was 0.0007, 0.0008 and 0.001 g/mg.min, respectively. The adsorption isotherm followed Langmuir model (average R2 = 0.873), with the adsorption capacity being 2.357, 1.198, and 8.196 mg/g, respectively, and the pore volume being 0.0316, 0.0364 and 0.2103 L/mg, respectively.